Scheme of the Zone Around the Well - Bobomurodov Utkir Ziyadullaevich (Scientific Trends, 2024)
The main elements of the zone around the well are the thickness of the reinforcing steel pipe from the inner surface of the operational column, the cement layer, the mud shell, the clomatization zone, the washed zone, the entrance zone, and then the uncontaminated part of the formation. It can be seen that the filtration-volume characteristics of the zone around the well are significantly different from the rest of the layer. The closer we get to the operating column, the more noticeable this difference is. In addition, the degree of negative filtration-volume property depends on the layer saturated with liquid or gas and how the rock is used. If the formation is saturated with natural hydrocarbon gas and the rock is hydrophilic, then this difference is the largest, and if the rock is hydrophilic and the formation is saturated with water, then the difference is the smallest amount.